Tremblay, Tony, The Fiddlehead Moment: Pioneering an Alternative Canadian Modernism in New Brunswick, Montreal and Kingston: McGill-Queen’s University Press, 2019 - MacLaren, Eli (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2026)
The Fiddlehead (1945–), published in Fredericton at the University of New Brunswick, is the longest-running literary magazine in Canada. What were the origins of The Fiddlehead, and how did it develop so successfully? These are the questions pursued by Tony Tremblay in his monograph, The Fiddlehead Moment: Pioneering an Alternative Canadian Modernism in New Brunswick (2019). This review summarizes Tremblay’s account of the magazine, describing the education and accomplishments of the three principals behind it: Alfred Goldsworthy Bailey (1905–97), Desmond Pacey (1917–75), and Fred Cogswell (1917–2004). The Fiddlehead thrived because these founders converted the political and economic disadvantages of twentieth-century New Brunswick into an “alternative modernism” that came to a head far from the metropolitan centres of Montreal, Toronto, New York, and London. Tremblay’s book demonstrates how literature can make a place. The review applauds this scholarly accomplishment, while noting, in its scholarly method, a tension between Marxism and liberal individualism.